Exploring the Oxidative Stress Mechanism of Buyang Huanwu Decoction in Intervention of Vascular Dementia Based on Systems Biology Strategy - Yang, Kailin (Oxid Med Cell Longev, 2021)
OBJECTIVE: To explore the oxidative stress mechanism of modified Buyang Huanwu decoction (MBHD) in intervention of vascular dementia (VD) based on systems biology strategy. METHODS: In this study, through the reverse virtual target prediction technology and transcriptomics integration strategy, the active ingredients and potential targets of MBHD treatment of VD were analyzed, and the drug-disease protein-protein interaction (PPI) network was constructed. Then, bioinformatics analysis methods are used for Gene Ontology (GO) enrichment analysis and pathway enrichment analysis, and finally find the core biological process. After that, in animal models, low-throughput technology is used to detect gene expression and protein expression of key molecular targets in oxidative stress-mediated inflammation and apoptosis signaling pathways to verify the mechanism of MBHD treatment of VD rats. Finally, the potential interaction relationship between MBHD and VD-related molecules is further explored through molecular docking technology. RESULTS: There are a total of 54 MBHD components, 252 potential targets, and 360 VD genes. The results of GO enrichment analysis and pathway enrichment analysis showed that MBHD may regulate neuronal apoptosis, nitric oxide synthesis and metabolism, platelet activation, NF-κB signaling pathway-mediated inflammation, oxidative stress, angiogenesis, etc. Among them, SIRT1, NF-κB, BAX, BCL-2, CASP3, and APP may be important targets for MBHD to treat VD. Low-throughput technology (qRT-PCR/WB/immunohistochemical technology) detects oxidative stress-mediated inflammation and apoptosis-related signaling pathway molecules. The molecular docking results showed that 64474-51-7, cycloartenol, ferulic acid, formononetin, kaempferol, liquiritigenin, senkyunone, wallichilide, xanthinin, and other molecules can directly interact with NF-κB p65, BAX, BCL-2, and CASP3. CONCLUSION: The active compounds of MBHD interact with multiple targets and multiple pathways in a synergistic manner, and have important therapeutic effects on VD mainly by balancing oxidative stress/anti-inflammatory and antiapoptotic, enhancing metabolism, and enhancing the immune system.